2015
DOI: 10.3189/2015jog14j120
|View full text |Cite
|
Sign up to set email alerts
|

Former dynamic behaviour of a cold-based valley glacier on Svalbard revealed by basal ice and structural glaciology investigations

Abstract: ABSTRACT. Large numbers of small valley glaciers on Svalbard were thicker and more extensive during the Little Ice Age (LIA), demonstrated by prominent ice-cored moraines up to several kilometres beyond present-day margins. The majority of these glaciers have since experienced a long period of strongly negative mass balance during the 20th century and are now largely frozen to their beds, indicating they are likely to have undergone a thermal transition from a polythermal to a cold-based regime. We present evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 95 publications
(231 reference statements)
2
46
0
Order By: Relevance
“…Tectonic deformation is evident within the thin debris laminae in the dispersed facies, which often display a strong linear component indicative of shear (Figure 3b). Such features within basal ice sequences have been termed stretching lineations [e.g., Fleming et al, 2013;Lovell et al, 2015] and are similar to stringers commonly described from glacitectonized sediments [e.g., Roberts and Hart, 2005].…”
Section: Dispersed Faciesmentioning
confidence: 92%
“…Tectonic deformation is evident within the thin debris laminae in the dispersed facies, which often display a strong linear component indicative of shear (Figure 3b). Such features within basal ice sequences have been termed stretching lineations [e.g., Fleming et al, 2013;Lovell et al, 2015] and are similar to stringers commonly described from glacitectonized sediments [e.g., Roberts and Hart, 2005].…”
Section: Dispersed Faciesmentioning
confidence: 92%
“…The persistence of warm‐based active ice differs from recently documented changes in thermal regime from warm‐ to polythermal or cold‐based (e.g. Lovell et al ., ; Reinardy et al, ) and observed stagnation (e.g. Bradwell et al ., ) as a result of thinning at modern glaciers.…”
Section: Controls On Recession Patternsmentioning
confidence: 99%
“…Hambrey et al, 2005;Lovell et al, 2015), with many glaciers in Svalbard receding and thinning substantially since their Neoglacial maxima (c. 1900 AD). As climatic warming is most pronounced in the polar regions, it is necessary to understand how Arctic glaciers will respond to ongoing climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The upwards migration of equilibrium lines and pronounced surface lowering of glaciers in Svalbard have revealed the internal structure of many ice masses in unprecedented detail. Recent structural glaciological research in Svalbard has primarily focused on structural controls on entrainment and transport of debris in polythermal and cold-based glaciers (Bennett, Hambrey, Huddart, & Ghienne, 1996;Boulton, van der Meer, Beets, Hart, & Ruegg, 1999;Hambrey & Glasser, 2003;Hambrey, Dowdeswell, Murray, & Porter, 1996;Hambrey, Bennett, Dowdeswell, Glasser, & Huddart, 1999;Hambrey et al, 2005;Hubbard, Glasser, Hambrey, & Etienne, 2004;Lovell et al, 2015). The map described in this paper documents the glacier-wide structural characteristics of Austre Brøggerbreen, a cold-based valley glacier in Svalbard.…”
Section: Introductionmentioning
confidence: 99%